Finite element simulation of three surgical treatments of distal radius intra-articular fracture - Shirazi, Arash Nasrollahi (2010)
Distal radius fractures are the most common injuries, with an estimate overall crude incidence of 36.6/10,000 person-year in women and 8.9/10,000 person years in men. Assuming a continuous rise in the incidence of distal radius fractures with age, and based on the fact that older population continues to grow, incidence of distal radius fractures can be expected to increase. Different surgical methods can be used to fix the complicated, unstable and displaced distal radius fractures. The conventional surgical method with volar plating has been described the good results in young patient. However, the elderly patients especially who has the osteoporotic bone may have higher risk of loss of reduction in conventional types of fixation. The aim of this study is to compare the latest treatment angle-stable constructs with conventional model for unstable three fragmental intar-articular distal radius fracture (AO 23-C2.1) under various load conditions using finite element analysis in order to find the stiffer surgical methods to facilitate the anatomic reduction and maintenance of the reduction. The fixation methods consist of 1 I-shape styloid plate and 1 intermediate dorsal plate (Group 1), single T-shape volar plate (Group 2) and 1 Ishape styloid plate and single T-shape volar plate (Group 3). This study analysed the rigidity base on linear load-displacement graph. To compare the rigidity, the fixation methods analysed under the applied loads (axial-loads, bending and torsion). The displacement and von Mises stress values showed the superior stability and rigidity for angle-stable double plates constructs.